Human rights and the evolution of international norms. - Forde, Henry (1990)
Contends that only a strict adherence to the naturalist approach can provide Caribbean states with the necessary societal cohesiveness to proceed and develop as states. Argues that the perception of vulnerability to intervention that derives from smallness and location in a sphere of influence has led to the adoption of the statist approach to the protection of human rights in the Caribbean, with the consequent insistence of non-interference and non-intervention as international norms.